PRODUCTION OF CLEAN DIESEL OILS - A.S. Nasution; E. Jasjfi; Evita H. Legowo (Scientific Contributions Oil and Gas, 2005)
Cars and fuels have been developed simultaneously and nowadays cars demand a very sophisticated fuel indeed. Environmental restriction and efforts to minimize the pollution problem by exhaust gases are causing de- sign changes in cars that in turn are having some effects on fuel quality. The development of processes for making high cetane number gas oil blending components and the widespread use of additives to enhance fuel properties have all contributed to the highly developed motor fuel used today". Gas oil components produced in the refineries generally consist of predominantly straight-run gas oil (SRGO) obtained from the fractional distillation of crude oils. There are two types of straightrun gas oil ie a sulfur rich (0.9-1.9 wt.%) aromatic source, and a low- sulfur (<0.2 wt.%) paraffinic crude source121, To satisfy the growing demand for diesel fuel, increased use of cracked stocks is anticipated. The primary requirement in diesel oil properties is that it should burn smoothly, without exploding, under the condition existing in the combustion chamber, so that maximum amount of useful energy is liberated. The ignition quality of a diesel oil is measured by its cetane number, which depends on its hydrocarbon composition. Different refineries produce diesel oil of different compositions, depending on the blending components available. Hydrocarbon compositions of the gas oil components show marked variation in their precombustion and ignition characteristics and so differ in their combustion behavior in an engine. Such a selective hydrocracking process has the following reaction: desulfurization, denitrogenation, deoxygenation, saturation and isomerization which could improve the flowing properties of gas oil components: sulfur, nitrogen, polycyclic aromatics and total aromatics, product stability, colour, neutralization number and distillation temperature (T50 and T90). The properties of the straight-run and cracked gas oil components, and improving their quality by a hydrotreating process to meet the clean diesel oil specification and production of gas oil components in Indonesia's refineries are described. A brief deliberation is offered on the impact of the changing diesel oil quality requirement, particularly due to the environmental restriction, on the refinery configuration.